Faktor Sukses E-Government dalam Pelayanan Perizinan Melalui Surabaya Single Window (SSW) Alfa di Kota Surabaya - Septian, Eric; Kriswibowo, Arimurti (Jayapangus Press, 2024)
E-government implementation in Indonesia is faced with several obstacles, including regulatory conflicts, limited facilities, shortage of human resources, and lack of public understanding. Surabaya City Government successfully overcame these challenges by launching Surabaya Single Window (SSW) Alfa application for licensing. The purpose of this research is to explain and analyze e-government success factors in Licensing Services through Surabaya Single Window (SSW) Alfa in Surabaya City. The research method used is a qualitative case study method written descriptively using e-government success factors. Data collection was done through interviews, observation, and documentation. The results obtained in this study are 1) DPMPTSP Surabaya City and DINKOMINFO Surabaya City have a clear assessment basis and questionnaires to assess the quality of the SSW Alfa application, 2) DPMPTSP Surabaya City and DINKOMINFO Surabaya City have maintained the quality of staff skills through internal training and provided various facilities related to staff skills for other OPDs, 3) There is still a shortage in the availability of human resources, but in handling public complaints, DPMPTSP Surabaya City provides various channels. 4) DPMPTSP of Surabaya City and DINKOMINFO of Surabaya City have had basic regulations as a reference for the implementation of SSW Alfa, and overcome budget constraints by using the general budget, 5) There are constraints on the limited number of ICT human resources at DINKOMINFO Surabaya City, as well as additional human resources at DPMPTSP Surabaya City to support the Public Service Mall (MPP).